Developing Literacy Learning Based on Big 6 Using Snowball Throwing - Ulum, Bahrul; Utami, Ima Wahyu Putri; Amelia, Delora Jantung (FKIP - Universitas Riau, 2025)
This study aims to develop and test the effectiveness of the literacy learning based on the BiG 6 model combined with the Snowball Throwing technique to improve critical thinking, problem-solving, and collaboration skills of PGSD students. This research uses the Research and Development (R&D) method with the ADDIE model (Analyze, Design, Develop, Implementation, Evaluation). The research subjects were 3rd-semester PGSD students at Muhammadiyah University of Malang in the 2024/2025 academic year. Data collection techniques include observation, questionnaire, documentation, and effectiveness test using N-gain calculation. Validation was carried out by two experts, namely literacy experts and learning strategy experts. Literacy expert validation results of 3.78 are included in the very good category. Validation results from model expert validators amounted to 3.47 in the good category. The effectiveness of the model is in the moderately effective category with an N-gain value of 66.4%. Student response to the model showed a high level of interest, with a percentage of 92.4%. literacy learning based on Big 6 using Snowball Throwing is proven to be able to create valid, effective and interesting learning, and improve students' information literacy skills.